Integrin α2β1 in nonactivated conformation can induce focal adhesion kinase signaling - Maria Salmela; Johanna Jokinen; Silja Tiitta; Pekka Rappu; R. Holland Cheng; Jyrki Heino (Scientific Reports, 2017)
Abstract Conformational activation of integrins is generally required for ligand binding and cellular signalling. However, we have previously reported that the nonactivated conformation of α2β1 integrin can also bind to large ligands, such as human echovirus 1. In this study, we show that the interaction between the nonactivated integrin and a ligand resulted in the activation of focal adhesion kinase (FAK) in a protein kinase C dependent manner. A loss-of-function mutation, α2E336A, in the α2-integrin did not prevent the activation of FAK, nor did EDTA-mediated inactivation of the integrin. Full FAK activation was observed, since phosphorylation was not only confirmed in residue Y397, but also in residues Y576/7. Furthermore, initiation of downstream signaling by paxillin phosphorylation in residue Y118 was evident, even though this activation was transient by nature, probably due to the lack of talin involvement in FAK activation and the absence of vinculin in the adhesion complexes formed by the nonactivated integrins. Altogether these results indicate that the nonactivated integrins can induce cellular signaling, but the outcome of the signaling differs from conventional integrin signaling.